(untitled) (Journal of Hama University, 2020)
Patients’ acceptance of an orthodontic appliance may influence compliance and thus contribute to a successful outcome of treatment. The aim of this study was to compare patients acceptance between Herbst and Korn MA fixed functional appliances by patients and assess degree of pain, tension of oral soft tissues and restriction of mandibular movement.30 patients with skeletal class II malocclusion were equally dividided into two groups. For each 15 patients (Female and male) with age ranged (12-15) yrs. Questionnaire was based on four-point scale (1,2,3,4) for questions regarding pain, tension of oral soft tissues and restriction of mandibular movement. The results of this study indicated patients’ acceptance for both appliances used in this study and this accommodation was better in Korn MA regarding oral soft tissue tension, pain and restriction of mandibular movement. oral soft tissue tension, pain and restriction of mandibular movement were occurred when applying both fixed functional appliances (Herbst and Korn MA) only during the first two weeks, then gradually decreased within three months until they finally faded in the remainder of the treatment.